Uji Efek Anti-Inflamasi Virgin Coconut Oil Terhadap Penurunan Volume Edema Telapak Kaku Tikus Putih Jantan Galur Wistar yang Diinduksi Karagenan - Rahman, Adam Nur, Devi Usdiana Rosyidah (2017)
Background: Inflammation is a body protective response against foreign agents or lesion. Inflammatory effects such as swelling, heat, pain, and loss of function. NSAIDs are revolving have adverse side effects. Virgin Coconut Oil (VCO) is one of the flagship products in Indonesia as a tropical country is considered to have anti-inflammatory effects. Objective: To determine whether there is an anti-inflammatory effect of Virgin Coconut Oil (VCO) against foot edema volume decrease in carrageenan induced strain Wistar male rats Research Methods: The test method carrageenan induced inflammatory use pretest-posttest with control group design. Test animals used were 25 strain wistar male rats were divided into 5 groups: positive control group (Diclofenac Sodium 1,82 mg/kg), negative control group (Aquadest), treatment group I (VCO 4 g/kgBB), group treatment II (VCO 6 g/kgBB), and the treatment group III (VCO 8 g/kgBB). Results: Based on the Kruskal-Wallis test VCO administration group at minute doses of 180-200 obtained significant probability values (p = 0.001) thus p <0.05 then the effect on the group 5 there are significant differences to the decline in the volume of edema. Then proceed with the Mann Whitney test to compare each group and the results obtained: Aquadest : Diclofenac Sodium=0.008, Aquadest : VCO 4 g/kgBB =0.032, Aquadest : VCO 8 g/kgBB=0.016. Thus p <0.05 or significantly different. Conclusion: The results showed that Virgin Coconut Oil (VCO) with a dose of 4g /kgBB and 8 g/kgBB body weight can lower the volume of edema in the minutes to 180-300 with edema volume reduction percentage are respectively 2,47% and 4,17%. The optimal dose in reducing edema volume was a dose of 8 g/kgBB with a percentage of 4,17%. Keyword: Virgin Coconut Oil, VCO, Anti-Inflammatory, Carrageenan.